THE USE OF DIGITAL LEARNING MEDIA IN EFL CLASSROOM FOR WRITING SKILLS - Azadat Wiqoyatin Nur; Lathifa Faza Ramadhani (JEELL (Journal of English Education, Linguistics and Literature), 2025)
Writing is an important skill in EFL classrooms; unfortunately, teaching still faces challenges, especially in the digital era. Digital tools for learning media can offer significant solutions, but they’re still inconsistent when used in writing instruction. This study aimed to identify the most commonly used digital tools and analyze their effectiveness in improving EFL students’ writing skills. Using a qualitative method through systematic literature review, there were forty studies from 2022 to 2025 were analyzed. The results showed that there are three main types of digital learning media, which are AI-based tools, social media platforms, and collaborative writing tools. Among them, ChatGPT and Instagram were found to be the most frequently used and effective in enhancing students’ grammar, vocabulary, motivation, and writing confidence. These findings have suggested that when applied digital tools are used purposefully, they can significantly support writing development in EFL classrooms.